2018
DOI: 10.1515/eujal-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive discourse functions in Austrian CLIL lessons: towards an empirical validation of the CDF Construct

Abstract: It is now widely recognized among educators that explicit attention to language is necessary in order to optimize both language and content learning in situations, such as CLIL, where learners, teachers or both operate in a second language. However, the requirement of attention to language sits uneasily with the fact that content-subject specialist teachers frequently feel unprepared to think and operate in linguistic dimensions. In an attempt to create a conceptualisation that would speak to subject teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 5 publications
2
17
0
Order By: Relevance
“…In terms of the Implemented Curriculum, our analysis of CDFs within Episodes revealed both similarities and differences with the Austrian findings of Dalton-Puffer et al (2018). A main similarity is that CDFs were a staple of teaching and learning, but that they are not equally distributed, occurring in varying degrees of frequency.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In terms of the Implemented Curriculum, our analysis of CDFs within Episodes revealed both similarities and differences with the Austrian findings of Dalton-Puffer et al (2018). A main similarity is that CDFs were a staple of teaching and learning, but that they are not equally distributed, occurring in varying degrees of frequency.…”
Section: Discussionmentioning
confidence: 53%
“…Within each of these Tasks, data was coded at the 'Episode Level'. An 'Episode' was defined as a 'longer stretch of talk serving one overall communicative function' (Dalton-Puffer et al, 2018). Each Episode was coded with one or more of Dalton-Puffer's (2013) seven basal CDF categories that best described the communicative intention.…”
Section: Codingmentioning
confidence: 99%
“…2 These types are neither disjunct nor mutually exclusive, creating somewhat fuzzy categories, which, according to Dalton-Puffer (2013), would allow the accommodation of different (subject-) cultural models. This CDF-Construct has been empirically validated for different subjects in a number of MA-theses, summarized in Dalton-Puffer et al (2018). Furthermore, Dalton-Puffer and Bauer-Marschallinger (2019) have shown that the CDF-Construct is compatible with competency-based history education as conceptualized in the Austrian context, both from a theoretical and empirical point of view, indicating that CDFs could work well to operationalize the integration of subject and language learning.…”
Section: Operationalizing the Integration Of Content And Language: Cognitive Discourse Functionsmentioning
confidence: 89%
“…This is now where the concept of Cognitive Discourse Functions (CDFs) comes in, which will be presented in more depth in the following section. CDFs can be defined as communicative patterns that are routinely used to express thought processes and appear to be an integral part of subject pedagogies, too (Dalton-Puffer et al, 2018). These language patterns very often overlap with curricular Bauer-Marschallinger, S. subject goals, which tend to be expressed with the help of performative verbs, as exemplified by the following samples taken from the Austrian curriculum for upper secondary history education (Austrian Federal Ministry for Education, 2014):…”
Section: Operationalizing Content and Language Integration Via Cognitmentioning
confidence: 99%